2018
DOI: 10.1021/acssynbio.8b00222
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Cell-Free Vibrio natriegens Expression System

Abstract: The fast growing bacterium Vibrio natriegens is an emerging microbial host for biotechnology. Harnessing its productive cellular components may offer a compelling platform for rapid protein production and prototyping of metabolic pathways or genetic circuits. Here, we report the development of a V. natriegens cell-free expression system. We devised a simplified crude extract preparation protocol and achieved >260 μg/mL of superfolder GFP in a small-scale batch reaction after 3 h. Culturing conditions, includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 35 publications
4
75
0
Order By: Relevance
“…Moreover, Garschagen et al (2019) recently showed that V. natriegens biomass increases remarkably after 24 h at 37 • C under conditions of SMG, and the final cell population can reach 60-fold that of cells grown at normal gravity (1 g). V. natriegens is a non-pathogenic, fast-growing marine bacterium doubling twice as fast as Escherichia coli, and several studies have documented that it would be the next-generation microbial chassis for the normal molecular biology and biotechnology applications, including molecular cloning (Weinstock et al, 2016;Dalia et al, 2017;Lee et al, 2019), protein synthesis (Schleicher et al, 2018;Wiegand et al, 2018;Eichmann et al, 2019), and small molecule production (Hoffart et al, 2017;Long et al, 2017), etc. The rapid growth rate of V. natriegens makes it a more promising engineering strain as an alternative workhorse to Escherichia coli (Hoff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Garschagen et al (2019) recently showed that V. natriegens biomass increases remarkably after 24 h at 37 • C under conditions of SMG, and the final cell population can reach 60-fold that of cells grown at normal gravity (1 g). V. natriegens is a non-pathogenic, fast-growing marine bacterium doubling twice as fast as Escherichia coli, and several studies have documented that it would be the next-generation microbial chassis for the normal molecular biology and biotechnology applications, including molecular cloning (Weinstock et al, 2016;Dalia et al, 2017;Lee et al, 2019), protein synthesis (Schleicher et al, 2018;Wiegand et al, 2018;Eichmann et al, 2019), and small molecule production (Hoffart et al, 2017;Long et al, 2017), etc. The rapid growth rate of V. natriegens makes it a more promising engineering strain as an alternative workhorse to Escherichia coli (Hoff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In order to tackle these problems, several new CFPS systems have recently been developed to better mimic the physicochemical environment of native hosts for synthetic biology and biotechnology applications. However, the newly developed CFPS systems are mainly derived from prokaryotic microorganisms, including some from Streptomyces species (Li et al, 2017(Li et al, , 2018aMoore et al, 2017), Bacillus subtilis (Kelwick et al, 2016), Pseudomonas putida (Wang et al, 2018), and Vibrio natriegens (Des Soye et al, 2018;Failmezger et al, 2018;Wiegand et al, 2018). Although a couple of eukaryote-based CFPS systems are available, they are mostly prepared from plant (e.g., wheat germ), insect (e.g., Spodoptera frugiperda), and mammalian (e.g., Chinese hamster ovary, CHO) cells (Tarui et al, 2001;Takai et al, 2010;Brödel et al, 2014), which often need laborious and expensive cell extract preparation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Third, this approach does not rely on time-consuming enzyme purification procedures but rapidly builds and tests metabolic pathways directly in cell extracts by synthesizing required enzymes in vitro (Karim et al, 2018;Karim and Jewett, 2016). Given these advantages, cell-free systems have emerged as an important approach for accelerating biological design, especially with the advent of new extract based systems from non-model organisms: Bacillus (Moore et al, 2018), Streptomyces (Li et al, , 2017, Vibrio (Des Soye et al, 2018;Failmezger et al, 2018;Wiegand et al, 2018), and Pseudomonas among others. However, no clostridia cell-free system exists that produces protein yields sufficient for prototyping genetic parts and metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%